Mayotte s'ancre dans la république française - François Taglioni (EchoGéo)
The geographical field of the French administration jurisdiction will evolve in 2011 with the creation of the 101st department: Mayotte. This departmentalization outside the hexagon is the result of a long political process begun in 1975 to the date of the first referendum that would thereafter Mayotte separate from the rest of the Comoros archipelago. This departmentalization comes within a social and political instability particularly acute for several months in the French overseas departments. It appears as a paradox in the history of the French overseas, and overseas from other countries in the world, which generally seek to escape the tutelary power instead of being assimilated.